Problemy dostosowania i harmonizacji prawa Republiki Czeskiej z prawem WE/UE: [Problems of approximation and harmonization of the law of Czech Republic with EC/EU law] (Studia Prawnicze / The Legal Studies, 2006)
Proces zbliżania prawa RCz do przepisów prawa WE rozpoczął się jeszcze w czasach istnienia czechosłowackiej federacji na podstawie Umowy o Handlu, Współpracy Handlowej i Gospodarczej z maja 1990 r. i powinien być kontynuowany na podstawie Tymczasowego Porozumienia między Wspólnotą Europejską a CSRF z grudnia 1991 r., które nie weszło jednak w życie z powodu rozpadu CSRF i powstania samodzielnej Republiki Czeskiej i samodzielnej Republiki Słowackiej.Wyraźnym impulsem do dostosowania porządku prawnego RCz do europejskiego prawa wspólnotowego stała się Umowa Stowarzyszeniowa (US), ustanawiająca stowarzyszenie między Republiką Czeską z jednej strony a Wspólnotami Europejskimi i ich państwami członkowskimi z drugiej, która weszła w życie 1 lutego 1995 r. Z umowy tej wynikały całkiem konkretne zobowiązania RCz dotyczące harmonizacji prawa narodowego z prawem WE. Zbliżanie prawa narodowego do przepisów prawa Wspólnot stało się znaczącym warunkiem integracji gospodarczej RCz z WE. Harmonizacja przepisów prawa nie dotyczy jedynie prawa obowiązującego, ale również przyszłych przepisów i ma istotny wpływ na tworzenie prawa na wszystkich płaszczyznach integracji RCz ze strukturami europejskimi. The approximation of the law of the Czech Republic with Community law took place in the conditions of CR association with EC defined by the European Agreement, establishing the association between the Czech Republic on the one hand and the European Communities and their member states on the other hand, which entered into force on 1 February 1995. The preparation of the Czech Republic for its entry to EC/EU was govemed by the Programme of CR Preparation for EU Membership, drafted and updated by the Govemment of the CR in 1999 and 2000 respectively. For this purpose it defined in particular the tasks aimed at the achievement of the compatibility of CR law with EC/EU law, the compliance with the conditions of CR integration in EU common market, the assurance of integration measures, the harmonization of legal regulations and their enforcement as well as the involvement of the Czech Republic in EU structural policies. In the course of CR association with EU also the constitutional background of CR entry in EU was assured. Art. 1 Oa of the Constitution of the Czech Republic makes it possible to transfer some sovereign powers of CR organs to an international organization or institution by an international treaty and the new wording of Art. 10 provides that the promulgation of such an intemational treaty ratified by the Parliament forms part of the national legal system and is superior to laws.The necessary changes in legislation and organization resulted in an acceleration of the legislative process concerning the harmonization of CR law with EC/EU law particularly due to the close co-operation of the Government with the Parliament.With regard to the accession of CR to EU ( on 1 May 2005) the procedural rules of both the Chamber ofDeputies and of the Senate were so amended as to enable the CR Parliament to join effectively in the decision-making of EU organs, in particular the Community legislation. Also new Methodological Instmction of the Government for the assurance of the works related to the fulfilment of the obligations arising from CR membership in EU were adopted ( on 12 October 2005).In conclusion the author points out some problems of the relation of national legislation and EU legislation. Apart from positive features the Europeization of national legal systems has also some shortcomings. Community legislation is obviously rightly criticized for its fragmentary character and insufficient flexibility due to inconsistent application of the principle of subsidiarity. The legal system of EU requires the codification of its fundamental legal principles and vast simplification and purification of its legal regulations. In this respect the draft of the European Constitution, regardless of its further fate, has brought about a number of proposals for the division of legislative competences between the Union and its member states as well as for effective participation of member states in the making of Community law in accordance with the principles of subsidiarity and proportionality.